The Relationship between Supervisor Support and the Developmental Trajectories of Mental Health among Graduate Students in a Medical School - Wang, Qiuyue; Xiao, Jian (Journal of Theory and Practice in Education and Innovation, 2024)
To understand the developmental trajectories of the mental health of graduate students in medical schools in China over a 3-year period and explore relationships with supervisor support to provide a scientific basis for promoting the mental health of graduate students in medical schools. For the longitudinal study, 448 graduate students from different classes in the 2020 class in a medical school in China were selected via a cluster sampling method. The University Personality Inventory (UPI) scale was administered to the participants in September 2020, and the UPI scale and the supervisor support scale were administered again in June 2023. The developmental trajectories of mental health among graduate students in medical schools were categorized into four groups: the healthy group (78.35%), deterioration group (9.6%), improvement group (6.92%), and persistent underlying psychological symptoms group (9.13%). Supervisor support and type of specialty were significantly different among the four groups (p<0.05). The results of logistic regression revealed that graduate students in clinical specialties were more likely to experience deterioration (OR = 2.415; 95% CI: 1.257–4.643) or improvement (OR = 2.622; 95% CI: 1.238–5.553) in their mental health. Compared with high supervisor support, low supervisor support was more likely to lead graduate students in medical school to experience deteriorated mental health (OR = 3.622, 95% CI: 1.52–8.631) and persistent underlying psychological symptoms (OR=5.661; 95% CI: 1.556–20.591). From enrollment to graduation, the level of psychological symptoms of graduate students in medical school has shown an increasing trend. Low supervisor support can predict the developmental trajectory of their mental health status, and universities should develop effective measures to improve supervvisor support and alleviate the mental health problems of graduate students.